CLASSICAL MUSIC IN THE WORLD OF EDUCATION: SONG SELECTION FOR HELPING TO LEARN - Fadhilla Pradnya Ningtias; Adhitya Pratama Irwanto; Khaikal Ridwan Taufik Siregar; Raja Khumala Nasution; Atiqah Salma Azahra (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the effect of classical music on high school students' concentration. Classical music, especially that which is in accordance with the Mozart Effect theory, is believed to improve cognitive performance and concentration. The methods used are literature studies and simple experiments to observe students' responses when studying with classical music. The results of the study indicate that classical music, with its stable and harmonious rhythmic characteristics, helps create a more conducive learning atmosphere, improves concentration, and reduces stress. Recommendations for classical songs are also given to support learning.